The Cocoa Production Systems of the Shushufindi Canton and its Resilience to Climate Change - Albiño Cargua, Jose Iván (2020)
In Shushufindi, a city located in Sucumbíos province from Ecuador, cocoa (Theobroma cacao) has become an important part of the economy, being the most representative crop of the families's productive systems. Due to the economic dependence created, cocoa  crop have a greater risk to disturbances. The objective of the present investigation was evaluate the climatic resilience of cocoa production systems through the methodology proposed by Córdoba (2016, 148) for the evaluation of the resilience and climate variability in the agroecosystems. This methology was adapted to the context of the place of study. Ten production systems: five monocultures (MN) and five agroforestry systems (AF) were analyzed. In these systems, 46 resilience indicators grouped into 11 criteria and aspects were evaluated: biophysical, social, health, cultivation practices, soil management, diversity, self-consumption, organizational, technical, performance and economic. The production systems and their components were georeferenced by aerial photography. One sample plot per system was selected to collect data about plants diversity and soil organic matter (MO). Each indicator was initially evaluated on a scale from 0 to 5 and then was multiplied by a weighting coefficient. The AF systems showed greater resilience than the MN systems in 10 of the 11 criteria analyzed (except performance). However, in both production systems is necessary to potentiate key aspects for improve their adaptation and transformation capacities to climate change. Keywords: agroforestry; cocoa; climate change; production systems; resilience